Studi Kelayakan Produksi Briket dari Kayu Karet dan Sekam Padi Sebagai Upaya Diversifikasi Energi Berkelanjutan - Suripto, Heri; Anwar, Saiful; Hamid, Abdul (Accurate: Journal of Mechanical Engineering and Science, 2023)
This research aims to evaluate the feasibility of producing briquettes from rubber wood and rice husks as a step towards sustainable energy diversification. Qualitative and quantitative analyses were conducted on the raw materials, considering their physical and chemical properties as well as calorific values. The production process involves drying, grinding, mixing, compacting, and forming using simple technology. Feasibility study results show positive attributes of the briquettes, with low ash content at 1%, high calorific value at 5016 kJ, and low moisture content at 0.9%. Briquettes offer potential as clean and efficient energy sources. Economic analysis reveals an NPV of IDR 407,729 and an IRR of 20%, surpassing the 12% case of capital rate. Overall, this briquette production signifies a viable and sustainable energy diversification effort, contributing to environmentally friendly energy source development.